A cobertura da Estratégia Saúde da Família e sua relação com indicadores de saúde no Brasil: a série histórica 1999-2019 - Luana Maria Guerra Juventino Dias (2022)
The Family Health Strategy (FHS) was created as an alternative to change the assistance model of Primary Health Care. Analyzing the relationship of its coverage with health indicators makes it possible to identify its effects and the impacts of public policies. This dissertation seeks to analyze the association between the evolution of a set of twelve health indicators in Brazil and the coverage of the FHS in Brazilian municipalities, from 1999 to 2019. An ecological study was carried out with a temporal quantitative approach and analysis of secondary data of national scope. The databases used were: SIAB (Primary Care Information System), SINASC (Live Birth Information System), SIPNI (National Immunization Program Information System), SIM (Mortality Information System), SIA (Outpatient Information System), IBGE (Brazilian Institute of Geography and Statistics), SISAB (Health Information System for Primary Care), SIH-SUS (Hospital Information System of the Unified Health System), IPEA (Institute for Economic Research Applied), SCNES (National Registry of Health Establishments System) and ANS (National Supplementary Health Agency). The annual averages of twelve municipal indicators were the dependent variables and the main independent variable was the coverage by the FHS. Parametric and non-parametric tests were used to verify the association between the indicators with the year, FHS coverage, Gini index, Social Vulnerability Index (SVI), population size, coverage by Community Health Agent and by private health plans. To measure the correlation between numerical variables, Spearman's correlation was used. The Generalized Equations Estimating model was used to assess the trend of the indicators and the comparison of their averages in relation to the coverage of the FHS and other independent variables. The Stepwise method was used to select the control variables and a 5% significance level was adopted for the multiple model. With the increase in the Gini Index or SVI, eleven indicators worsened, mainly for the proportion of teenage pregnancy and infant mortality rate (IMR). Only the proportion of live births with low birth weight proved to be lower the greater the increase in these indices, which is related to maternal and health care characteristics. FHS coverage improved indicators related to prenatal care, vaccination coverage and the number of visits performed by doctors and nurses in Primary Care. The IMR showed a reduction, but with a slight increase at the end of the observed period. Neonatal mortality has become more significant in the composition of this rate in Brazil, being more sensitive to care provided mainly by specialized and hospital services outside the scope of the FHS. The effect of FHS coverage on the indicators remained significant and increased as coverage increased, even after controlling for confounding variables. Social determinants were shown to have an important impact on the health indicators included in this study, which reinforces the importance of the FHS as a fundamental strategy to guarantee equitable and universal access.